Biosynthesis of zinc oxide nanoparticles using water hyacinth extracts: Characterization, evaluation of antimicrobial and dye removal - SONTHONGPHITHAK, Phiphat; MUANGNAPOH, Chonchanok; RATANATAWANATE, Chalita; E-KOBON, Teerasak; PIYASAENGTHONG, Akkharadet; HONGSACHART, Piyorot; SRIUTTHA, Manop; SENGKHAMPARN, Nipaporn; DHANAPAL, Anto Cordelia Tanislaus Anthony; WITTAYANARAKUL, Kitiyaporn (Journal of Metals, Materials and Minerals, 2024)
In nanobiotechnology, synthesizing metal nanoparticles (NPs) using plant extracts has recently been increasing because of eco-friendly and low-cost methods. For this work, zinc oxide nanoparticles (ZnO NPs) have been synthesized by biosynthesis process using water hyacinth extracts (WHE). The water hyacinth (WH) was chosen because the WH is fast-growing and the most toxic aquatic plant in the world. Therefore, this work aims to apply these WHE to be a precursor in the biosynthesis of ZnO NPs (ZnOBio-NPs) based on the research of a sustainable environment. The ZnO NPs synthesized by the WHE were investigated for their antibacterial and photocatalytic activities. An UV-Vis spectrum showed a specific absorbance peak around 362 nm with an average band gap of 3.22 eV. As the result, TEM analysis revealed a triangle structure with an average size of about 64.05 nm. The peaks of XRD analysis show a hexagonal wurtzite structure. The ZnO NPs synthesized by the WHE showed higher antibacterial activity against S. aureus better than E. coli. It is interesting to note that the ZnOBio-NPs synthesized from the WHE can have an anti P. acnes (JB7) with a minimum inhibitory concentration (MIC) and a minimum bactericidal concentration (MBC) equal to 50 µg∙mL‒1 and 200 µg∙mL‒1, respectively. In addition, the ZnOBio-NPs also can effectively remove more than 90% of the malachite green within 180 minutes with extremely high reuse.